Inclusão na educação superior: operacionalização das acessibilidades nas práticas pedagógicas com discentes surdos - MEDEIROS, Aline Mendes (2023)
The inclusion of deaf students in Higher Education depends on several factors, ranging from access to information to the pedagogical practices applied by professors for their permanence in the institution. The present study aimed to analyze the operationalization of communicational, methodological, and instrumental accessibility in pedagogical practices for the inclusion of deaf students in higher education in the Brazilian Sign Language Course. The qualitative, descriptive, exploratory, documentary, and field research through case study was carried out at the Federal University of Piauí, Campus Universitário Ministro Petrônio Portella between the periods of 2020.1 to 2021.2, corresponding to the years 2021 and 2022, still in the period of the Corona Virus Disease 2019 (COVID-19) pandemic. The participants were 7 professors from the Letters-Brazilian Sign Language course at the Center for Human Sciences and Letters, 3 male, and 4 female, with an average age ranging from 20 to 50 years, training in teaching in the areas of Pedagogy, Geography, and Letters – Brazilian Sign Language; and a bachelor's degree in Business Administration, Accounting Sciences and Technology in Human Resource Management, mostly with a specialization in Brazilian Sign Language. In data collection, official documents from the aforementioned University were used, such as the Institutional Development Plan, the Pedagogical Project of the course in focus, and semi-structured interviews. Data from documents and interviews were submitted for content analysis. The results of the research indicated that the Institutional Development Plan dealt with the issue of communicational, methodological, and instrumental accessibility in a comprehensive way, suggesting that some of the institution's bodies were promoters of this accessibility, for example, the Accessibility Center and the Department of the Language Course - Brazilian Sign Language. The Pedagogical Project of the course in question also addressed these three types of accessibility in a broad way and directed that the Structuring Teaching Center of the course should always check the best way to enable accessibility in the course, through more appropriate methodologies and pedagogical practices. Among these methodologies and appropriate pedagogical practices, it was obtained as a response from the referred nucleus that the explanation of classes with deaf students occurred preferably in LIBRAS. Specifically in relation to the operationalization of accessibility by teachers, the results showed that most of them had specialization and fluency in Brazilian Sign Language, enabling its use as the main means of communication to contemplate communication accessibility. Regarding methodological accessibility, teachers encouraged the active participation of students with visual resources, materials in videos with subtitles, and activities and assessments varied between theoretical and practical procedures. Instrumental accessibility was operationalized through audiovisual materials, videos translated into Brazilian Sign Language, applications with 3D avatars, and digital platforms such as Kahoot, YouTube, and Google Meet. It is concluded that communicational, methodological, and instrumental accessibility are aspects under development in the pedagogical practices of the professors of the analyzed course, but some points still need to be expanded and described in official documents and in the production of instruments and teaching materials used in the education of deaf students.